Pathology of Experimental Velogenic Viscerotropic Newcastle Disease (VVND) in House Sparrows and Australian Parrots: Disease in House Sparrows and Parrots (Biological Sciences - PJSIR, 2023)
The pathology of experimental VVND was studied in twelve birds of house sparrows (S) and Australian parrots (P) which were divided into 6 equal (n= 4) experimental groups viz. S1, S2, S3, P1, P2, P3 and one group of broilers (C). The groups S1 and P1 (intramuscularly), groups S2, P2 and C (orally) were administered with 0.3 mL of VVND virus (2.3x1010.73 EID50). The groups S3 and P3 were kept in contact exposure with group C. The susceptibility and pathology were compared by measuring parameters like clinical scores, mortality rate, mean death time (days), necropsy findings, lesion scores and histopathological findings. Moreover, anti-VVND virus antibody (HAI) titers were measured in surviving birds. Yellow greenish diarrhoea, messy feathers, torticollis and anorexia were the main clinical signs observed in groups S1, S2, P1 and P2. However, no symptoms were observed In groups S3 and P3. The mean clinical scores of the three groups were statistically non-significant (P > 0.05). In contrast to Australian parrots, house sparrows have a higher mortality rate. The mortality rate observed in groups S1, S2, P1, P2, S3 and P3 was 100%, 75%, 50%, 50%, 0% and 0% respectively. The difference in mean death time (days) was not statistically meaningful (P > 0.05). The proventriculus, small intestine, spleen and trachea of all the infected birds had histopathological lesions. Precise hemorrhages in the proventriculus, defined button like lesions of the intestinal epithelium and necrosis in the trachea and spleen are among the necropsy lesions of infected birds. Haemagglutination inhibition (HAI) titer on day 21 was found to be higher in all the experimental groups. In conclusion, both house sparrows and Australian parrots are vulnerable to experimental VVNDV infection intramuscularly and orally, with house sparrows being more susceptible. Sero-conversion was seen in contact exposed groups without VVND clinical signs.